2009
DOI: 10.1039/b903903a
|View full text |Cite
|
Sign up to set email alerts
|

“Clickable” elastins: elastin-like polypeptides functionalized with azide or alkyne groups

Abstract: Elastin-like polypeptides (ELPs) functionalized with azide or alkyne groups were produced biosynthetically and coupled via the Cu-catalyzed azide-alkyne cycloaddition to a variety of (bio)molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…13 The use of chemoselective reactions to selectively modify specific residues in ELPs post-synthesis has been shown to be a promising means to introduce new functionalities and impart new properties to ELPs, especially at their chain ends, 14,15,16,17 and more scarcely at ELP side-chain residues. 18,19 In a previous study, we reported the chemoselective alkylation of all methionine (Met) residues in the ELP sequence (VPGMG) 20 , which contains Met residues in every repeat, and used this modification to tune the LCST of the resulting polysulfonium ELP derivatives. 20 However, a limitation of this system was the need to use hydrophobic alkylating reagents, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…13 The use of chemoselective reactions to selectively modify specific residues in ELPs post-synthesis has been shown to be a promising means to introduce new functionalities and impart new properties to ELPs, especially at their chain ends, 14,15,16,17 and more scarcely at ELP side-chain residues. 18,19 In a previous study, we reported the chemoselective alkylation of all methionine (Met) residues in the ELP sequence (VPGMG) 20 , which contains Met residues in every repeat, and used this modification to tune the LCST of the resulting polysulfonium ELP derivatives. 20 However, a limitation of this system was the need to use hydrophobic alkylating reagents, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…20 Modifications at the amino acid side chains within the ELP domain have been more scarcely reported. 21,22 Such modifications require the use of highly efficient reactions in order to successfully modify all the repeating functional groups in these sequences in high yield. These modifications also require the use of bioorthogonal ligation strategies to chemoselectively modify residue-specific side chains without affecting the amino acid backbone, C-and N-terminal ends and side chain groups of other residues.…”
Section: Introductionmentioning
confidence: 99%
“…Van Hest and coworkers [237] developed a clickable ELP via RSI of Aha and Hpg. A fluorescent protein-polymer hybrid was synthesized by reacting a coumarin-functionalized PEG2000-bearing azide with Hpg-ELP via Cu (I)-catalyzed azide-alkyne cycloaddition.…”
Section: Future In Combined Technologies To Fabricate Tailored Proteimentioning
confidence: 99%
“…A fluorescent protein-polymer hybrid was synthesized by reacting a coumarin-functionalized PEG2000-bearing azide with Hpg-ELP via Cu (I)-catalyzed azide-alkyne cycloaddition. In addition, the azide-functionalized CalB generated via RSI of Aha [221] was conjugated to Hpg-ELP, shifting the LCST behavior from the ELP to the CalB, while maintaining 50% of its hydrolytic activity relative to the conjugated Aha-CalB [237].…”
Section: Future In Combined Technologies To Fabricate Tailored Proteimentioning
confidence: 99%